IMPLEMENTASI PEMBENTUKAN RANCANGAN PERATURAN WALI KOTA SURABAYA TENTANG POSYANDU BERDASARKAN UNDANG-UNDANG PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN - Moch. Rafli Wahyu Dwi Saputra; Adhitya Widya Kartika (Legal Standing : Jurnal Ilmu Hukum, 2026)
This research addresses the low level of public understanding regarding the procedure for drafting the Surabaya Mayor Regulation (Raperwali) on Posyandu, despite the mechanism being regulated in Law No. 12 of 2011 on the Formation of Laws and Regulations and its implementing provisions. The limited knowledge of the stages of planning, drafting, deliberation, ratification, and promulgation creates a gap between the normative process conducted by the local government and community involvement as stakeholders. This study employs a descriptive qualitative approach through field research and document analysis. Primary data were obtained from in-depth interviews with officials involved in the drafting process, while secondary data were collected from legal and administrative documents. The findings indicate that the drafting of the Surabaya Mayor Regulation on Posyandu generally complies with applicable statutory provisions; however, several obstacles remain, including limited human resources, the lack of legal drafting experts, and lengthy bureaucratic procedures. Therefore, although the regulation has a valid legal and procedural basis, strengthening transparency, cross-sectoral coordination, and institutional capacity is necessary to enhance its effectiveness and legitimacy. Ultimately, the Mayor Regulation on Posyandu serves not only as an administrative legal instrument but also as a means of community empowerment in supporting the achievement of Minimum Service Standards (SPM) in public services.